7m-3-2=(5m-2)+6

Simple and best practice solution for 7m-3-2=(5m-2)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7m-3-2=(5m-2)+6 equation:


Simplifying
7m + -3 + -2 = (5m + -2) + 6

Reorder the terms:
-3 + -2 + 7m = (5m + -2) + 6

Combine like terms: -3 + -2 = -5
-5 + 7m = (5m + -2) + 6

Reorder the terms:
-5 + 7m = (-2 + 5m) + 6

Remove parenthesis around (-2 + 5m)
-5 + 7m = -2 + 5m + 6

Reorder the terms:
-5 + 7m = -2 + 6 + 5m

Combine like terms: -2 + 6 = 4
-5 + 7m = 4 + 5m

Solving
-5 + 7m = 4 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.
-5 + 7m + -5m = 4 + 5m + -5m

Combine like terms: 7m + -5m = 2m
-5 + 2m = 4 + 5m + -5m

Combine like terms: 5m + -5m = 0
-5 + 2m = 4 + 0
-5 + 2m = 4

Add '5' to each side of the equation.
-5 + 5 + 2m = 4 + 5

Combine like terms: -5 + 5 = 0
0 + 2m = 4 + 5
2m = 4 + 5

Combine like terms: 4 + 5 = 9
2m = 9

Divide each side by '2'.
m = 4.5

Simplifying
m = 4.5

See similar equations:

| -6a-18=-2a+2 | | 5n+9=49 | | 0.5x=1.25 | | 1.1x=-12.1 | | 5x+8x-9x=8+4 | | 30=3x+x+6 | | 4x+19-2x=9+5x-5 | | -17=3x | | 8b+6b+6=3b+21 | | -8=3x+9 | | 85+c/4=99 | | 13=x-5x-7 | | y^2+2y+17=0 | | 31+x/7=150 | | m(m+6)=40 | | 3.2y+6.4=6.4 | | 3b+8-(b+2)=4b+14-(2b+8) | | x=2+8(x-12) | | 2s^2=5s-12 | | 2+2x+x=-25 | | 3x+7x=16+9x | | 2a+3-8=5a+12-3a | | 7x=-23 | | 5t+10=10t+60 | | 0.2(x+30)-0.6(x-20)=10 | | 3x+7x=x-6 | | 6.4s+3.3=12.5 | | 44=30-2(x-2) | | 2x+8=4x-(10-4x) | | 10x-(7x-5)=11 | | 4u-8=5(1-u) | | x^4-8x^3+15x^2+4x=20 |

Equations solver categories